Etos Kerja Pedagang Etnis Madura di Pusat Grosir Surabaya Ditinjau Dari Etika Bisnis Islam - Muhammad Ersya Faraby; Siti Inayatul Faiza (Universitas Airlangga, 2014)
Natural resources have not been well managed in Madura and the low level of human resources leads to ethnic Madurese communities abroad to obtain a decent life by applying a high work ethic. This research aims to know the work ethic of ethnic Madurese in Central merchant Wholesale Surabaya reviewed from Islamic business ethics.Approach used in this research is qualitative approach to method case study is descriptive. Data done with interview observation and documentation against traders ethnic madura in central wholesale Surabaya. For data advocates derived from data given by centers management wholesale Surabaya. Besides is also study library and literature about ethos work ethnic Madurese and Islamic business ethics.The results obtained are the informants argued most of the Madurese ethnic merchants in wholesale center Surabaya interpret and apply the Madurese ethnic work ethic that is hard work and wander, as well as in implementing the work ethic they comply with Islamic business ethics. REFERENCESAfifuddin dan Beni Ahmad Saebani. 2009. Metodologi Penelitian Kualitatif. Bandung: Pustaka Setia.Asifudin, Ahmad Janan. 2004. Etos Kerja Islami..Surakarta: Muhammadiyah University Press.Al-Quran Indonesia, 2013. Tanpa Judul. (Online), (http://www.alquranindonesia.com/, diakses 2 September 2013, jam 00: 52.Amalia, Fitri. 2012. Implementasi Etika Bisnis Islam Pada Pedagang Di Bazar..Madinah..Depok..(Online),. (https://www.google.com/#q=Im plementasi+Etika+Bisnis+Islam+Pa da+Pedagang+Di+Bazaar+Madin ah+Depok&spell=1,diakses 22 Oktober 2013, jam 22.15).Anjani, Sarah. 2012. Etos Kerja Pedagang Etnis Madura Di Perkotaan. Surabaya, Universitas Airlangga (Skripsi Tidak Diterbitkan).Baron and P. David. 2006. Business and it’s environment, 5th ed. Upper Saddle River, New Jersey: Pearson Education Inc.Bertens, K. 2000. Pengantar Etika Bisnis. Yogyakarta: Kanisius.Carroll, A. B. and Buchholots. 2005. Business and Society: Ethics and Stakeholder Management, Santa Fe: South-Western College Publication.Chaplin, J.P. 2001. Kamus Psikologi (Terjemahan: Kartono, K). Bandung: CV. Pionir Jaya.Daft, Richard L. 2007. Manajemen 6thed. Ahli Bahasa Oleh Edward Tanujaya dan Shirly Tiolina. Jakarta: Salemba Empat.Elts, P. Van der. 1925. De Madoereezzen. De Taak 8: 421-428.Embse, Von der and Wagley, R.A. 1988. Managerial Ethics Hard Decisions on Soft Criteria. Advance Managemen Journal.Emzir. 2010. Metode Penelitian Kualitatif: Analisis Data. Jakarta: PT. Raja Grafindo Persada.Faizah, Siti Inayah. 2012. Kewirausahaan dalam Perspektif Agama dan Budaya (Studi Fenomenologi Konstruktif Wirausahawan Etnis Tionghoa Muslim). Surabaya, Universitas Airlangga (Tesis Tidak Diterbitkan).Hageman, J. 1858. Bidragen tot de kennis van de residentie Madoera. Tijdschrift voor Nederlandsch Indië 20, 1: 321-352.Handoko, Hani. (1993-2001). Manajemen Personalia dan Sumber Daya Manusia. Yogyakarta: BPFEYogyakarta.Hisrich, Robert, et al. 2008. Entrepeneurship: Kewirausahaan. Edisi tujuh. Jakarta: Salemba Empat.H.,’t. 1924. De stierenwedrennen op Madoera. De Aarde en Haar Volken 60-8: 179-182.Iga Manuati Dewi. 2002. Makalah. Mengapa dan Untuk Apa Orang Bekerja?. Bali: Universitas Udayana.Imron, D.Z. 1996. Peta Estetik Madura Masa lalu. Dalam Mahasin, A. et al. (penyunting). Ruh Islam dalam Budaya Bangsa: 2. Aneka Budaya di Jawa. Jakarta: Yayasan Festival Istiqlal: 293-299.Indarti, Nurul dan Rostianti, Rokhima. Jurnal Ekonomika dan Bisnis Indonesia, Vol.23, No. 4, Oktober 2008. Jonge, H. de. 1989. Madura Dalam Empat Zaman: Pedagang, Perkembangan Ekonomi Dan Islam. Jakarta: KITLV-LIPI-PT Gramedia.—————–. 1995. Stereotypes of the Madurese. Dalam Dijk, K. Van, Jonge, H. De & TouwenBouwsma, E. (penyunting). Across Madura Strait: The Dynamic of an Insular Society. Proceedings KITLV 2: 7-24.Kattsoff, Louis O and Pent. Soejono Soemarjono. 1996. Pengantar Filsafat. Yogyakarta: Tiara Wacana Yogya.Keraf, A.Sonny. 1998. Etika Bisnis: Tuntutan dan Relevansinya, Yogyakarta: Kanisius.Kuntowijoyo. 2002. Perubahan Sosial dalam Masyarakat Agraris Madura 1850-1940. Yogyakarta: Matabangsa.Madjid, Nurcholis. 1995. Islam Agama Kemanusiaan..Jakarta: Paramadina.Meredith, Geoffrey. 2002. Kewirausahaan Teori dan Praktek. Jakarta: Pustaka Binaman Pressindo Mitis. 1903. De kerapan sapie (stierenwedren). Een Madureesch feest. Eigen Haard 21: 334-336.Moleong, J. Lexy. 2008. Metodologi Penelitian Kualitatif. Bandung: Remaja Rosda Karya.Nadjib, E.A. 2005. Folkore Madura. Yogyakarta: Progres.Nazir, Mohammad. 1988. Metode Penelitian. Jakarta: Ghalia Indonesia.Ni’am, Ulin. 2012. Etos Kerja Komunitas Pedagang Etnis Sunda di Desa Besito..Kecamatan..Gebog..Kabu paten..Kudus..(Online),.(https://w ww.google.com/#q=Etos+Kerja+ Komunitas+Pedagang+Etnis+Sun da+di+Desa+Besito+Kecamatan+ Gebog+Kabupaten+Kudus, diakses 22 Oktober 2013, jam 22.10).Nitisemito, Alex 1996. Manajemen Personalia (Manajemen Sumber Daya Manusia). Kudus: Ghalia Indonesia.Ramiza,..Abu...2011...Sumpah..Palsu...(Onli ne),.(http://aburamiza.wordpress. com/tag/sumpah-palsu/, diakses 27 Oktober 2013, jam 15.48).Rifai, Mien Ahmad. 2007. Manusia Madura. Yogyakarta: Pilar Media.Rivai, Veithzal. 2012. Islamic Business and Economic Ethics. Jakarta: PT Bumi Aksara.Rudito, Bambang dan Famiola. 2007. Etika Bisnis dan Tanggung Jawab Sosial Perusahaan Indonesia. Bandung: Rekayasa Sains.Shatahah, Husain dan Siddiq. 2007. Transaksi dan Etika Bisnis Islam. dalam Kamus Al-Iqtishod wat-Tijaroh Aroby – Inglizy. Beirut – Libanon.Slamet, E.J. 1996. Perilaku Ekonomi Masyarakat Madura. Dalam Mahasin, A. et al. (penyunting). Ruh Islam dalam Budaya Bangsa: 2 Aneka Budaya di Jawa. Jakarta: Yayasan Festival Istiqlal: 357-373.Spradley, James P. 1997. Metode Etnografi. Terjemahan oleh Misbah Zulfa Elizabeth. Yogyakarta: Tiara Wacana Yogya.Subaharianto, Andang, dkk, 2004, Tantangan Industrialisasi Madura Membentur Kultur, Menjunjung Leluhur, Malang: Bayumedia.Suhamijaya, S. 2000. Membina Sikap Mental Wirausaha. Jakarta: Gunung Agung.Sugiyono, 2011. Metode Penelitian Pendidikan: Pendekatan Kuantitatif, Kualitatif, dan R&D. Bandung: Alfabeta.Surink, H.A. 1933. Zeden en gewoonten op ‘t eiland Madoera. De Aarde Haar Volken 69-10: 195.Suryana. 2003. Kewirausahaan. Edisi Pertama. Jakarta: Salemba Empat.———-, 2011. Kewirausahaan Pedoman Praktis: Kiat dan Proses Menuju Sukses. Jakarta: Salemba Empat.Syahrial, Muhammad. 2011. Anakku Maukah Kau jadi Pengusaha? Mengapa harus jadi Pengusaha?. Seri 1. Jakarta: PT. Lentera Ilmu.Syamsuddin, Muh.,